Estado de coisa: memória e violência em Fábrica de Chocolate, de Mario Prata - Santos, Lucelia (2017)
Whether being a body of human life's world, by taking the body of the citizen as an object, the State denies its own life's possibility, even before killing it. And if by killing it, denies that did it, making himself as a double criminal: by murder and by lying. Chocolate Factory, Mario Prata's theatrical text, written in 1979, deals exactly with one of the moments in which a worker is reduced to the condition of a thing in the hands of his torturers/murderers, a crime that is transformed into a suicide by the State. The aim of this dissertation is to analyze this theatrical text, using the concepts of lie – and its bound with a memory - of allegory to demonstrate the fiction' process of the engendered violence through the action of torturing, murdering and lying and its policy consequence. Therefore, a dialogue with works, among them "History of the Lie: prolegomena" by Jacques Derrida, "Truth and Politics", by Hannah Arendt, "Memory, Forgetfulness, Silence" by Michael Pollak, "The Origin of German Tragic Drama", by Walter Benjamin, and "Homo Sacer: Sovereign Power and Bare Life" I, by Giorgio Agamben was crucial for this task's achievement.